Assessment of Knowledge, Attitude, and Practices toward Knee Pain and Its Various Treatment Modalities among Patients - Akhil Bhalla; Sidharth Verma; Sanjog Ramrao Mekewar; Sasmit Dipak Lotliker; Aanchal Sharma; Oshin Agrawal; Maitri Shah; Hritik Madan; Dhriti Sood (Indian Journal of Pain)
Background: This cross-sectional study investigates the knowledge, attitudes, and practices regarding knee pain and its treatment modalities among patients in India. Aims: The aim of this study was to identify the prevalent beliefs, barriers to quality treatment, and factors influencing knee pain management. Settings and Design: This was a cross-sectional, multicentric survey. Materials and Methods: The study was conducted using a prestructured, prevalidated online questionnaire comprising 30 items in each section. Before data collection, the research received ethical approval from the Institutional Ethical Committee of Adesh Medical College and Hospital, Shahabad, Haryana. Data collection was done over a period of 3 months from various outpatient department-based settings using a nonprobability type, convenience sampling. A total of 731 participants were obtained in the study time frame who returned the completed questionnaire. Statistical Analysis: Tests of significance such as the Chi-square tests were used to find any associations between the categorical and ordinal variables. Some association between certain variables was also calculated using the Chi-square tests on the SPSS version 27 wherever required. Results: The study encompassed 731 participants, predominantly aged 30–70 years. Knee pain was reported by 80.8% of participants, with the most common diagnosis being knee osteoarthritis. Most participants consulted a doctor within a month, but a significant portion delayed seeking medical attention. Pain severity varied, with mild pain being the most reported. The majority relied on medical practitioners for information but also turned to nonprofessional sources. Conservative therapy with medication was the most common treatment. A significant knowledge gap existed regarding advanced interventional procedures, with only a small fraction aware of options such as platelet-rich plasma injections and other minimally invasive interventions. Overall, there was a high level of satisfaction with conservative management, but awareness and utilization of advanced treatment options were low. Conclusion: The study reveals substantial knee pain prevalence among adults, primarily attributed to osteoarthritis, with a significant impact on daily activities and quality of life. Despite a high reliance on medical practitioners for information, there are abundant misconceptions regarding the condition and significant delays in seeking treatment. Conservative management remains the preferred approach, but there is limited awareness of advanced interventional treatments. Enhancing patient education on knee pain causes, treatment options, and the benefits of minimally invasive procedures is crucial for improving management and outcomes. Addressing these gaps can lead to better pain management strategies and reduced disease burden, especially in resource-constrained settings like India.